Anoro Ellipta: dry powder LAMA/LABA combination for COPD. Issue 4 (19th February 2015) - Chaplin, Steve
<x xml:space="preserve">Abstract</x> Anoro Ellipta is the first inhaler to combine a LAMA and a LABA in a single unit. Here we present the clinical data relating to its efficacy and adverse events and look at its place in the management of COPD.